Estimates Of Genetic Parameters For Various Traits In Two Strains Of White Leghorn Chicken - Meshram, A.Y; Joshi , R.S.; Savaliya, F.P.; Singh , A.P. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The genetic and phenotypic parameters of body weight and egg production traits up to 40 weeks of age were estimated from sire component of variances and covariances in two strains of White Leghorn (IWN and IWP). Heritability estimate of total egg numbers produced up to 40 weeks age (TEN40) was high in IWN strain (0.543±0.139) and moderate (0.232±0.091) in IWP strain while other traits like body weight (BW), egg weight (EW), Age at first egg (AFE) etc. shows usual trends. Estimates of genetic correlation among production traits were of poor precision as they were associated with high standard errors.